Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

$$\int \frac{1}{x(x^2+1)}dx = ? $$

How to solve it? Expanding to $\frac {A}{x}+ \frac{Bx +C}{x^2+1}$ would be wearisome.

share|cite|improve this question
It's not that "wearwisome": $1= A(x^2+1) +x(Bx+C) $. Take $x=0$. Then $A=1$. Thus $B=-1$ (looking at the $x^2$ coefficients) and $C=0$ (looking at the $x$ coefficients). – David Mitra Jan 26 '13 at 19:37
up vote 1 down vote accepted

It is not hard to express it as partial fraction, if you write $1$ in the numerator as $x^2+1 - x^2$.

Hence, $$\dfrac1{x(x^2+1)} = \dfrac{x^2+1-x^2}{x(x^2+1)} = \dfrac{x^2+1}{x(x^2+1)} - \dfrac{x^2}{x(x^2+1)} = \dfrac1x - \dfrac{x}{x^2+1}$$ Hence, $$\int \dfrac{dx}{x(x^2+1)} = \int \dfrac{dx}x - \int\dfrac{x}{x^2+1}dx = \log(x) - \dfrac12 \log(x^2+1) + \text{ constant}$$

share|cite|improve this answer

You can consider

$\displaystyle \frac{1}{x(x^2 + 1)} = \frac{1 + x^2 - x^2}{x(x^2 + 1)}$.

share|cite|improve this answer

For this problem, yes, we can avoid it in various ways.

For example, rewrite our function as $\frac{x}{x^2(x^2+1)}$. Make the substitution $u=x^2$. Then $du=2x\,dx$ and we end up with $$\frac{1}{2}\int \frac{du}{u(u+1)}.$$ Now use simple partial fractions to get to $$\frac{1}{2}\int\left(\frac{1}{u}-\frac{1}{u+1}\right)\,du.$$

Or else you can make the substitution $x=\tan t$. After the smoke clears, you are trying to find $$\int \frac{\cos t}{\sin t}\,dt.$$ Now make the substitution $u=\sin t$.

Remark: But you should not try to avoid the partial fraction process, it is pleasantly algorithmic.

share|cite|improve this answer

*Just do it!*$\,$: break the integrand into partial fractions...

Using partial fractions is the most straightforward approach (and in this case, is hardly wearisome).

$$ \frac{1}{x(x^2 + 1)} = \frac{x^2+1-x^2}{x(x^2+1)} = \frac{\color{blue} {\bf{x^2+1}}}{x\color{blue}{\bf(x^2+1)}} - \frac{\color{blue}{\bf x}\cdot x}{\color{blue}{\bf{x}}(x^2+1)}=\frac1x - \frac{x}{x^2+1}$$
$$\text{So now you have}\;\;\;\int \dfrac{dx}{x(x^2+1)}\; = \;\int \dfrac{1}x\,dx - \int\dfrac{x}{x^2+1}\,dx$$ and I trust you can take it from here.

The more you work with partial fractions (i.e. practice, i.e.), the easier they are to work with, and the more quickly you'll see how to proceed in doing so.

share|cite|improve this answer

And just to make this problem unnecessarily complicated: $$I=\int\frac{dx}{x^2\left(x+\frac{1}{x}\right)}=\int\frac{dx}{\left(x+\frac{1}{x}\right)}-\int\frac{\left(1-\frac{1}{x^2}\right)dx}{\left(x+\frac{1}{x}\right)}=\frac{1}{2}\int\frac{d\left(x^2+1\right)}{x^2+1}-\int\frac{d\left(x+\frac{1}{x}\right)}{\left(x+\frac{1}{x}\right)}$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.